30 years of IJSE : festschrift in honour of Professor John O'Brien. - O'Brien, J. C. (John Conway); Nitsch, Thomas O. (International journal of social economics, 2005)
This e-book addresses the issue of emotion in healthcare organization. It reflects a more general and growing interest in the role of emotion across a range of academic disciplines. The articles selected for inclusion in this e-book therefore trace both the interpersonal nature of emotion, as well as how it can also span the individual and the organizational setting. In addition there are articles which look at the bridges into both the shadowy areas of organizational life like gossip, as well as the interface between personal and professional lives. The papers indicate a shared international.